Portable and Inexpensive Blue LED based UV-Vis Spectrophotometer with Smartphone Detector as a Chemistry Learning Innovation - Fa'ari Salsabiila; Laila Nur Rahmawati; Heny Muna Kholidah; Ari Syahidul Shidiq (The Faculty of Teacher Training and Education (FKIP), Universitas Sebelas Maret, Indonesia, 2023)
Effective study of chemistry requires access to complete and affordable laboratory equipment. Practical activities provide hands-on learning experiences and help students understand chemical concepts more easily. The spectrophotometer is a key instrument in chemistry labs, but its high cost and complex maintenance often make it unavailable in schools. This study aims to design and develop an inexpensive, simple, and portable UV-Vis spectrophotometer that offers quick analysis, making it accessible for high schools as a contextual chemistry learning tool. Experimental methods were employed in laboratories and chemistry classrooms, focusing on measuring solution content. The UV-Vis spectrophotometer was developed using LED light sources and smartphones as detectors and data processors. Integrating smartphones with the spectrophotometer for data reading represents a significant innovation. Testing revealed that the prototype demonstrated high accuracy and precision, with recovery values between 90-110% and precision test results below 2%, indicating good repeatability. The Limit of Detection (LOD) was found to be 0.43 ppm, and the Limit of Quantification (LOQ) was 20.99 ppm. Classroom implementation involved 23 students from a private school in Surakarta, using questionnaires and learning outcome tests. Results showed that the prototype effectively enhanced students' understanding of stoichiometry, with an 89.217% improvement. Additionally, 89.681% of students responded positively to using the prototype as a learning tool. This research demonstrates that a simple, portable, and affordable spectrophotometer can be developed as an interactive learning medium in high schools, significantly improving students' comprehension and engagement in chemistry. The prototype aligns with the principles of laboratory UV-Vis spectrophotometry and Lambert-Beer's law, where higher solution concentrations correspond to greater absorbance values.